Letter to Jane Tolmach from Frederick G. Dutton - Frederick G. Dutton:::::: (1961)
A letter to Jane Tolmach from Frederick G. Dutton, Special Assitant to the President. The letter forwards a pamphlet that was prepared by the U.S. State Department regarding the Berlin crisis.